1983
DOI: 10.1113/jphysiol.1983.sp014719
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of growth hormone secretion to sleep in the immature rat.

Abstract: SUMMARY1. The correlation between growth hormone (GH) secretion and the sleepwakefulness cycle in the 29-31 day-old male rat was studied by serial blood sampling through an intracardiac cannula at 10 min intervals from 12.00 to 18.00 h. E.e.g.s recorded continuously during the blood sampling period were scored into wakefulness and sleep, and the amount of sleep for every 10 min was plotted against the GH value as assessed by radioimmunoassay.2. The power spectrum analysis and the least-squares method applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 25 publications
5
34
0
Order By: Relevance
“…During the 6-h period the hematocrit fell by 20 %, but on the basis of our experience described previously (Kimura & Kawakami, 1982;Kawakami et al 1983) there seemed to be no significant effect on the health of the rat or on the weight gain afterwards. Further, this loss of blood was presumed not to be stressful for the rat, since GH secretion has been shown to be suppressed by stress (Kokka, Garcia, George & Elliott, 1972;Terry, Saunders, Audet, Willoughby, Brazeau & Martin, 1977), whereas secretion continued through the 6-h sampling period in immature rats (Kawakami et al 1983).…”
Section: Blood Samplingmentioning
confidence: 94%
See 3 more Smart Citations
“…During the 6-h period the hematocrit fell by 20 %, but on the basis of our experience described previously (Kimura & Kawakami, 1982;Kawakami et al 1983) there seemed to be no significant effect on the health of the rat or on the weight gain afterwards. Further, this loss of blood was presumed not to be stressful for the rat, since GH secretion has been shown to be suppressed by stress (Kokka, Garcia, George & Elliott, 1972;Terry, Saunders, Audet, Willoughby, Brazeau & Martin, 1977), whereas secretion continued through the 6-h sampling period in immature rats (Kawakami et al 1983).…”
Section: Blood Samplingmentioning
confidence: 94%
“…In a recent study using immature male rats, however, we obtained findings showing that bursts of GH secretion were synchronized with a sleep cycle which manifested an ultradian rhythm of approximately 3-0-h periodicity (Kimura & Kawakami, 1981;Kawakami et al 1983). It was indicated that the ultradian rhythm of the sleep-wakefulness cycle played a significant role in the regulation of GH secretion in the immature rat.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the immature rat, we have also demonstrated that the rhythm was linked to the time of day ; i.e., the secretory episode of GH occurred eight times a day around 03.00, 06.00, 09.00, 12.00, 15.00, 18.00, 21.00 and 24.00 h. A quite interesting fact discovered in the present experiment is that the PRL secretory episode seems to occur in almost the same time schedule as that for the GH secretory episode. Since it was shown that the GH secretory episode coincided with the sleep cycle in the immature rat (Kawakami et al, 1983a), it is possible that PRL secretion also coincides with sleep. Experiments on this are currently under way.…”
Section: Discussionmentioning
confidence: 99%